Javanese Taboo Language as Social Interaction among Teenagers from Different Socioeconomic Backgrounds - Fajar Susanto; Claudia Fira Inne Purwantoro; Tri Indrayanti (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2026)
The purpose of this study is to explain why teenagers from different socioeconomic backgrounds use the Javanese taboo language and how taboo language influences the teenagers’ social interaction. This study was designed with the ethnographic qualitative approach. Because the subject has been decided in advance, the case study approach was also used in addition to the ethnographic method in this study. The participants in this study were four teenagers, two from the upper-middle class and two from the lower middle class. Data were taken with direct observations, recordings, and interviews. The findings indicated that a cursing ‘cok’, a sort of Javanese taboo language, is most commonly utilized by teenagers. That taboo language has become a common part of adolescents’ communication, particularly among lower middle-class teenagers. Family environment and peer groups strongly influence the normalization of taboo expressions in everyday speech. Lower middle-class participants tended to use taboo language as a symbol of intimacy, solidarity, and emotional expression, while upper middle-class participants showed greater awareness and control in avoiding taboo expressions due to stricter parental guidance and social norms. The study concludes that taboo language among teenagers is closely connected to socialization, identity, and interactional context rather than simply impolite behavior. Socioeconomic background significantly shapes teenagers’ perceptions, habits, and regulation of taboo language in daily communication.